Pemanfaatan Limbah Tahu Sebagai Pupuk Cair untuk Meningkatkan Produktivitas Pertanian Berkelanjutan di Desa Grujugan - Safitrih, Irene May Widiyani; Setyawan, Agung; Citrawati, Tyasmiarni (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
This research examines the effectiveness of tofu liquid waste as liquid organic fertilizer in increasing plant growth and yield and improving soil quality. Carried out in Grujugan Village, this research used an experimental design with several different treatments, namely tofu liquid waste concentrations of 0%, 25%, 50% and 100%. The results showed that application of liquid waste at a concentration of 50% resulted in optimal growth, with a significant increase in plant height, number of leaves, and yield weight. In addition, soil quality analysis shows improvements in nitrogen, phosphorus and potassium content, as well as soil pH that is closer to neutral. This research emphasizes the potential of tofu liquid waste as an innovative solution for waste management and sustainable agriculture, and provides recommendations for wiser use in agricultural practices.